Pengaruh Pemahaman Pimpinan Sekolah tentang Sistem Pengendalian Intern Pemerintah (SPIP) terhadap Efektivitas dan Efisiensi Pengelolaan Keuangan Sekolah di Kota Madiun - Siti Zoebaidha; Payamta Payamta (Jurnal Akuntansi dan Bisnis, 2014)
This study discusses the impact of the understanding school leaders about the Government Internal Control System (SPIP) on the effectiveness and efficiency of the financial management of the school in Madiun. SPIP includes the components of control environment, risk assessment, control activities, information and communication and also monitoring. This research uses populations of all public school leaders in SMA/SMK/MA in Madiun with the number of 13 schools. This research use a census technique, which is a technique for determining the sample based on the entire population (Sugiyono, 2008: 67). The Result of descriptive statistics regarding the understanding of school leaders in Madiun on the SPIP shows that most school leaders have understood for SPIP. T test results for models 1 and 2 showed significant positive results. It is supported from R2 test results and regression test model 1 and 2. While the crosstabulasi variable analysis showed a significant correlation between the effectiveness and efficiency of the financial management of the school. This is reinforced by the results of the chi square test and it’s contingent coefficient.